Element 1360 and RNAi components contribute to HP1-dependent silencing of a pericentric reporter. - Haynes, K.A.; Caudy, A.A.; Collins, L.; Elgin, S.C.R. (Current Biology, 2006)
In eukaryotes, distinct regions of the genome are packaged as euchromatin (less condensed, more active) or heterochromatin (condensed, silenced). Studies in yeast, plants, and flies suggest that RNA interference (RNAi) is linked to heterochromatin formation and transcriptional silencing of transposable element (TE) sequences. We previously reported that insertion of a mobile hsp70-white reporter within 10 kb of a 1360 element on chromosome four of Drosophila melanogaster correlates with variegation (silencing). Here, we report small RNAs (approximately 23 nt) corresponding to 1360, indicating processing by the RNAi machinery. To directly test the ability of 1360 to silence a nearby gene in vivo, we introduced a P element construct carrying a single copy of 1360 upstream of the hsp70-white reporter into flies. This 1360 element contributes to HP1-dependent variegation at a pericentric insertion site, as demonstrated by a decrease in silencing after FLP-mediated removal of 1360. In euchromatin, 1360 is not sufficient to induce silencing, suggesting that proximity to pericentric heterochromatin and/or a high local TE density contributes to heterochromatin formation. Silencing of the 1360, hsp70-white reporter is sensitive to mutations in RNAi components. Our results implicate 1360 as a target for sequence-specific heterochromatic silencing through an RNAi-dependent mechanism.